2021
DOI: 10.1155/2021/4549221
|View full text |Cite
|
Sign up to set email alerts
|

iNOS Promotes the Development of Osteosarcoma via Wnt/β-Catenin Pathway

Abstract: Inducible nitric oxide synthase (iNOS), accompanied with protumor and antitumor activity, has been studied in multiple cancers. However, the role of iNOS expression in osteosarcoma (OS) is far from being fully understood. In present work, iNOS levels were detected in OS tissues and cell lines. Colony formation assay, Transwell assay, and fow cytometer were used to assess proliferation, migration, invasion, and apoptosis abilities in vitro after iNOS inhibition. Western blotting determined the expressions of iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Previous research has demonstrated that abnormal Wnt signaling is linked to human osteosarcoma, suggesting a genetic vulnerability that may be exploited in osteosarcoma therapy [ 19 ]. Inhibition of FUT4 expression in this study restrained the Wnt/β-catenin signaling pathway and hence the osteosarcoma cells' capacities to proliferate, invade and migrate, which is consistent with earlier results [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has demonstrated that abnormal Wnt signaling is linked to human osteosarcoma, suggesting a genetic vulnerability that may be exploited in osteosarcoma therapy [ 19 ]. Inhibition of FUT4 expression in this study restrained the Wnt/β-catenin signaling pathway and hence the osteosarcoma cells' capacities to proliferate, invade and migrate, which is consistent with earlier results [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, TNF-α can cause tumor-related endothelial cell apoptosis and tumor cell necrosis, and induce the expression of several immunomodulatory mediators [50,51]. iNOS plays a positive role in tumor apoptosis, and the up-regulation of iNOS was reported to stimulate apoptosis of osteosarcoma cells [52]. In this study, the fraction SPP-0.7 showed the strongest antitumor and immune-enhancing activities among the five polysaccharide fractions.…”
Section: Discussionmentioning
confidence: 66%
“…Abnormal signals in Wnt signaling pathway are closely related to the occurrence of various cancers [ 18 ]. Research has verified that Wnt signaling pathway can participate in the development of OS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%